George Orwell’s 1984 in Louis Althusser’s Perspective - Pertiwi, Yudhanita ((JELE) Journal Of English Language and Education, 2021)
This research elaborates how ideology operates in a state that applies totalitarian system according to a novel entitled 1984 by George Orwell.This research employs Althusser’s theory which identifies how an ideology places human beings as autonomous subjects in a connecting structure with relations inside it. At the beginning, human beings have been prepared to function in the structure. Moreover, Althusser has some concepts related to the state power, namely Ideological State Apparatus (ISA), Repressive State Apparatus (RSA) and resistance. The function of the state power lies on the state existence and its apparatuses. ISA and RSA are applied as a mechanism to establish the people subservience as a source of power production.The result of this study demonstrates that there is always response from the people in a totalitarian state which applies a tight control over the people by its ideological and repressive apparatuses. As a result, this response becomes an alternative ideology; in this study is socialism, which develops as a resistance towards totalitarianism. The socialists are the proletarians who insist on the equality in the law and economy. However, the state does not allow the movement of the socialist because it is considered as a threat to the state power. Consequently, the state quickly annihilates the socialists and their ideology.